Emigration, retour et agriculture dans un village de Trás-os-Montes (Portugal) - Nobre, Sílvia (1993)
As a complex phenomenon, migration leads necessarily to changes in the concerned societies, either the departure society or the destination one, the former being in most cases rural based with agriculture as a main activity. Setting as a research field that rural and agrarian society, this study tries to identify factors conditioning the migration flow. It also attempts to understand the mechanisms of a changing community due to the return of migrant people back to their original village. A case study conducted in Pinela, a village of Northeastern Portugal, permited a local approach to the outlined research topics. Information, gathered from inquire techniques and written sources of different nature, has been treated by means of data analysis methods. "Landownership expectation", as it was coded here, provides an explanatory basis for migration flow in Pinela. This factor corresponds to the area owned by a family divided by the number of their children, and assesses the possibilities for children to expect a continuity in agriculture and, hence, in the village. Moreover, former migrants back in the village are active changing agents, as they commit themselves in new and diversified activities at the community level, although remaining farmers as they originally were.